SUSTAINABLE INDUSTRY MANAGEMENT STRATEGIES IN OVOP PROGRAM WITH RAP-FIOVOP METHOD - Puspokusuma, R.A Aryanti Wardaya; Adhikara, Cooky T; Hartono, Hendry; Mohamed Zainal, Siti Rohaida (SEEIJ (Social Economics and Ecology International Journal), 2018)
One Village One Product (OVOP) is a successful method in agribusiness that has been applied in various modern countries in the world. With OVOP assists the Indonesiaâ€™s industry, it open wider opportunities for both domestic and international markets. OVOP method is expected to bring prosperity to its members both within the scope of agriculture, livestock, crafts and other sectors. In this study, sustainability status for OVOP Tofu/Tahu Industry in Utan Kayu, East Jakarta, are assessed from 5 dimensions; Economic Dimension, Social Dimension, Environmental Dimension and Physical Environment, Dimension of Technology, and Leadership Dimension. In order to achieve the research objectives, there are 25 attributes obtained and are analysed to see the sustainability effect of OVOP in Â Utan Kayu Tofu Industrial Center. This paper also discussed the formulation of alternative sustainable OVOP policies in this industry namely are; 1) Communication with government agencies in encouragement and support of OVOP development facilities; 2) Development of competent human resources; 3) Socializing technology investment; 4) to formulate welfare improvement policy for businessmen; 5) allocation of credit assistance and businessmen funds. All these findings are discussed in detail as the conclusion of this paper.